2012
DOI: 10.1016/j.adolescence.2012.05.007
|View full text |Cite
|
Sign up to set email alerts
|

The influence of emotional intelligence (EI) on coping and mental health in adolescence: Divergent roles for trait and ability EI

Abstract: Theoretically, trait and ability emotional intelligence (EI) should mobilise coping processes to promote adaptation, plausibly operating as personal resources determining choice and/or implementation of coping style. However, there is a dearth of research deconstructing if/how EI impacts mental health via multiple coping strategies in adolescence. Using path analysis, the current study specified a series of multiple-mediation and conditional effects models to systematically explore interrelations between copin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
115
0
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(145 citation statements)
references
References 49 publications
19
115
0
11
Order By: Relevance
“…It was found that EI moderated the relationship between stress and psychological health such that it strengthened the negative impact of stress on psychological health, which is aligned with previous studies (Davis & Humphrey, 2012a, 2012b. Stress is viewed as a continuum along which an individual may pass from a feeling of eustress to mild/ moderate distress, and then to severe distress.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…It was found that EI moderated the relationship between stress and psychological health such that it strengthened the negative impact of stress on psychological health, which is aligned with previous studies (Davis & Humphrey, 2012a, 2012b. Stress is viewed as a continuum along which an individual may pass from a feeling of eustress to mild/ moderate distress, and then to severe distress.…”
Section: Discussionsupporting
confidence: 83%
“…It was found that in conditions like economic deprivation, ability emotional intelligence (AEI) moderated outcomes by amplifying the depressive states. Similarly trait emotional intelligence (TEI) moderated the relationship between the stressor (effect of family dysfunction) by having a soothing effect on disruptive behavior (Davis & Humphrey, 2012a, 2012b. In one study focusing on nurses' health, those with a higher attention toward emotions experienced higher stress levels compared to those with a low level of EI (Landa, Lo, Martos, & Aguilar-luzo, 2008).…”
Section: Moderating Role Of Emotional Intelligencementioning
confidence: 96%
“…Those interventions designed to increase both ESE and EI have been shown to be effective (Dacre Pool & Qualter, 2012b). Other authors support this need for the development of ESE and EI, arguing that both promote positive ways of coping with stressful situations (Davis & Humphrey, 2012), which leads to effective adaptation (Keefer, Parker, & Saklofske, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Due to clear differences in measurement methods, the constructs of ability and trait EI are heterogeneous (Petrides, 2007(Petrides, , 2011. Empirical studies have reported weak or orthogonal relationships between them (Davis and Humphrey, 2012;Di Fabio and Saklofske, 2014), which, in turn, lead to different outcomes in the association between well-being and job performance (Martins et al, 2010;O'Boyle et al, 2011). In this study, we focus on trait EI, which is typically measured by self-report questionnaires.…”
Section: Theoretical Background Of Eimentioning
confidence: 99%